Growing Season Climate Variability and its Influence on Sauvignon Blanc and Pinot Gris Berries and Wine Quality: Study Case in Romania (2005-2015) - Nistor, E.; Dobrei, A.G.; Dobrei, A.; Camen, D. (South African Journal of Enology and Viticulture, 2018)
The purpose of our research was to find out what influence climatic variability in the growing season has on the berry and wine composition in two white grape varieties grown in the vineyard of Banat University of Agricultural Sciences and Veterinary Medicine from Timisoara, located in the western area of Romania. The quality and characteristics of the wines produced in a limited area is essentially due to the environment, including natural and human factors. Two white cool-intermediate climate grape varieties - Sauvignon Blanc and Pinot Gris were chosen to study the impact of climate change on the main characteristics of juice and wine. A number of 40 berries from each variety was chosen for phenol extraction, total soluble solids (sugar content), titratable acidity and pH determinations. Wine samples were analysed after one year of ageing in the bottle. Alcohol concentration was not majorly influenced by temperature and rainfall over the years. Some experimental years with hot weather were favourable for sugar accumulation in berries and wine respectively;therefore, potential alcohol also increased. In the last decade, annual and monthly variability of rainfall and temperature influenced the phenological cycle of grapevines most, delaying or accelerating the developing of foliar area, as well as the ripening and harvesting time, which has a direct influence on grapes and wine products.